Checklist of Termites (Blattodea: Isoptera): Southern Haryana - B, Bhanupriya; Kakkar, Nidhi; Gupta, Sanjeev Kumar (Asian Journal of Biological and Life Sciences)
This study is designed with the aim to provide checklist and distribution of termite species (Blattodea: Isoptera) of Southern Haryana. Termite is a seasonally encountered insect so the survey of sample collection has been made during two years (2020; 2021) of study periods. Several morphological parameters have been examined for both soldier as well as worker caste i.e., body color, antennae segments number, head length without mandible, head total length with mandible, head maximum width, body total length from tip of abdomen to the tip of mandibles, body maximum width, tarsal segments and tibial spur. A total of 26 termite species were classified based on the phenotypic features, belonging to 3 families, 4 sub-family and 8 genera. Out of 3 families, Termitidae Latreille, 1802 is the most diverse family comprising 22 species, 6 genera and 3 subfamilies. Out of 26, many termites species i.e., Angulitermes sp., Coptotermes emersoni, C. gestroi, Eremotermes neoparadoxalis, Microcerotermes baluchistanicus, M. newmani, M. raja, Neotermes kemneri, N, sp 2., and Odontotermes anamallensis are stated first time from Southern Haryana probably due to edge effect.
Keywords: Distribution; Southern Haryana.; Taxonomy; Termites